Mesophase Structure‐Enabled Electrostrictive Property in Nylon‐12‐Based Poly(ether‐block‐amide) Copolymers. Issue 9 (17th July 2019) - Wongwirat, Thumawadee; Wang, Minghuan; Huang, Yanfei; Treufeld, Imre; Li, Ruipeng; Laoratanakul, Pitak; Manuspiya, Hathaikarn; Zhu, Lei
Abstract: To search for alternative electrostrictive polymers and to understand the underlying mechanism, the structure‐ferroelectric/electrostrictive property relationship for nylon‐12‐based poly(ether‐ b ‐amide) multiblock copolymers (PEBAX) is investigated. Two PEBAX samples are studied, namely, P6333 and P7033 with 37 and 25 mol.% of soft poly(tetramethylene oxide) (PTMO) blocks, respectively. In both samples, poorly hydrogen‐bonded mesophase facilitates electric field‐induced ferroelectric switching. Meanwhile, the longitudinal electrostrictive strain (S1 )–electric field (E) loops are obtained at 2 Hz. Different from conventional poly(vinylidene fluoride‐ co ‐trifluoroethylene) [P(VDF‐TrFE)]‐based terpolymers, uniaxially stretched nylon‐12‐based PEBAX samples exhibit negative S1, that is, shrinking rather than elongation in the longitudinal direction. This is attributed to the unique conformation transformation of nylon‐12 crystals during ferroelectric switching. Namely, at a zero electric field, crystalline nylon‐12 chains adopt a more or less antiparallel arrangement of amide groups. Upon high‐field poling, ferroelectric domains are enforced with more twisted chains adopting a parallel arrangement of amide groups. Meanwhile, extensional S1 is observed for P6333 at electric fields above 150 MV m −1 . This is attributed to the elongation of the amorphous phases (i.e., amorphous nylon‐12 and PTMO). Therefore, competition between shrinking S1 from mesomorphic nylon‐12 crystals (i.e., nanoactuation) and elongational S1 from amorphous phases determines the ultimate electrostriction behavior in stretched PEBAX films. Abstract : Nylon‐12‐based poly(amide‐block‐ether) (PEBAX) elastomers exhibit unique electrostrictive property. Under a high poling field, the stretched, high nylon‐12 content PEBAX film shrinks in the longitudinal direction, whereas the low nylon‐12 content PEBAX film exhibits minimum electrostriction in shrinkage. This is explained by the competition between crystal shrinkage and amorphous phase elongation in semicrystalline PEBAX samples induced by a high electric field.